2013
DOI: 10.1128/aem.03751-12
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Microcystis Cyanophage Gene Diversification Revealed by Long- and Short-Term Genetic Analyses of the Tail Sheath Gene in a Natural Pond

Abstract: Viruses influence the abundance of host populations through virus-mediated host cell lysis. Viruses contribute to the generation and maintenance of host diversity, which also results in viral diversity throughout their coevolution. Here, to determine the phage gene diversification throughout the coevolution of host and phage in a natural environment, we investigated the genetic diversity and temporal changes in Microcystis cyanophage populations using a total of 810 sequences of the Ma-LMM01-type cyanophage ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…Our level of knowledge regarding the total diversity and genetic composition of environmental phages is minimal. Evidence suggests that communities of phages found in freshwaters are likely to represent a more complex cohort than that of their marine counterparts (Kimura et al 2013;Baker et al 2006), in congruence with the more heterogeneous nature of freshwater. Broadly speaking, in comparison to marine communities, freshwaters are understudied regardless, and so the scope of this expected greater diversity is unknown.…”
Section: Discussionmentioning
confidence: 92%
“…Our level of knowledge regarding the total diversity and genetic composition of environmental phages is minimal. Evidence suggests that communities of phages found in freshwaters are likely to represent a more complex cohort than that of their marine counterparts (Kimura et al 2013;Baker et al 2006), in congruence with the more heterogeneous nature of freshwater. Broadly speaking, in comparison to marine communities, freshwaters are understudied regardless, and so the scope of this expected greater diversity is unknown.…”
Section: Discussionmentioning
confidence: 92%
“…1). The mcy gene cluster and mechanism of production of the microcystin molecule may not affect the metabolic pathway or the mechanism of phage replication inside the host cell, which, as suggested by Kimura et al [33], depends mostly on the photosynthetic system of cyanobacteria.…”
Section: Dynamics Of Occurrencementioning
confidence: 96%
“…This could prevent the detection of subtle changes between phage genotypes occurring as a result of point mutations. In a study of Kimura et al [33], the analysis of phylogenetic affiliations based on a longer fragment of the g91 gene (approximately 500 bp) enabled diversification and identification of more than 400 phage genotypes. Therefore, the diversity of Microcystis specific phages in the context of long-term monitoring of the Sulejów Reservoir will be assessed in future studies using larger fragments of the g91 gene, as suggested by Kimura et al [33].…”
Section: -A Ca T Ca G C Gt T C Gt T T C G Gt Ac Tgt a Gt C G Gt G C Gmentioning
confidence: 99%
See 2 more Smart Citations